Novel structure with negative Poisson's ratio and enhanced Young's modulus. (15th March 2016) - Lu, Zi-Xing; Li, Xiang; Yang, Zhen-Yu; Xie, Fan
Abstract: In this paper, analytical and finite element (FE) simulations are carried out to calculate the in-plane Poisson's ratio and Young's modulus of a novel concept of structure with honeycomb-like configuration under uniaxial loading. Opposite to similar re-entrant honeycomb structures, the new unit cell topology adding a narrow rib in the well-known re-entrant cellular structure. The results obtained through the analytical and FE analysis show that adding a narrow rib in the unit cell of re-entrant honeycomb configuration gives rise to a cellular structure with significant enhanced Young's modulus compared to the classical re-entrant configurations exhibited in literature. The results also show an obvious linear relationship between Young's modulus and Poisson's ratio of the proposed design with the adding ribs' thickness changing. For its significant Young's modulus enhancement and convenient to predictions of in-plane mechanical properties (Young's modulus and Poisson's ratios), this layout can be considered as a possible basis to design new concepts of auxetic structures with special functions.